Культурно-просвітницька діяльність Крайових організацій НРУ на Півдні України наприкінці 1980-х – 1991 рр. - Михайлов, В. В.; Mihaylov, V. (My University, 2017)
UK: У статті на основі матеріалів державних обласних архівів і періодичних видань розглядається проблематика процесу національного відродження у Південній Україні наприкінці 1980-х – 1991 рр. Визначено регіональну специфіку функціонування крайових осередків НРУ на Півдні України. Розкрито основні форми та методи культурно-просвітницької діяльності регіональних організацій НРУ, встановлено роль неформалів у процесах українського національно-державного відродження. Також здійснено загальний огляд видавничої справи осередків Руху. Визначено внесок південноукраїнських осередків НРУ у розбудову національної державності наприкінці 1980-х –1991 рр. RU: В статье на основе материалов государственных областных архивов и периодических изданий рассматривается проблематика процесса национального возрождения в Южной Украине в конце 1980-х – 1991 гг. Определена региональная специфика функционирования региональных центров НРУ на юге Украины. Рассмотрены основные формы и методы культурно-просветительской деятельности региональных организаций НРУ, установлена роль неформалов в процессах украинского национально-государственного возрождения. Также осуществлен общий обзор издательского дела филиалов НРУ. Определен вклад южноукраинских организаций НРУ в строительстве национального государства в конце 1980-х – 1991 гг. EN: In the article on the basis of the state regional archives and periodicals the problematic of national revival process in the southern Ukraine in the late of 1980’s – 1991 are considered. The author generalizes the known and introduces into the scientific circulation the new facts, which help to show the role of the People’s Movement of Ukraine «Rukh» (PMU) regional organizations in the processes of modern national revival. The regional specificity of functioning of the PMU regional organizations in the South of Ukraine is defined. The basic forms and methods of cultural and educational activities of the PMU regional organizations are revealed, the role of informal in the processes of Ukrainian national state revival is established. Also, the general review of the publishing business is carried out, the level of influence of the PMU press on public opinion of the southern region is analyzed, contribution of the publishing activity to the governmental, cultural and spiritual revival of the land is examined. The contribution of the PMU regional organizations in the development of Ukrainian statehood during the collapse of the Soviet system in the late of 1980’s – 1991 is defined.
Культурно-просветительская деятельность региональных организаций НРУ на Юге Украины в конце 1980-х – 1991 гг.
Cultural and educational activity of the PMU regional organizations in the South of Ukraine in the late of 1980s-1991
Keywords: опозиційний рух; Народний Рух України; культурно-просвітницька діяльність; видавнича справа; Південна Україна; оппозиционное движение; Народное движение Украины; культурно-просветительская деятельность; издательское дело; Южная Украина; oppositional movement; People’s Movement of Ukraine («Rukh»); cultural and educational activity; publishing activity; South Ukraine